2020
DOI: 10.3389/fpls.2020.01282
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Analysis and Molecular Marker Development for a New Wheat–Thinopyrum ponticum 1Js (1D) Disomic Substitution Line With Resistance to Stripe Rust and Powdery Mildew

Abstract: Thinopyrum ponticum (2n = 10x = 70), a member of the tertiary gene pool of wheat (Triticum aestivum L.), harbors many biotic and abiotic stress resistance genes. CH10A5, a novel disomic substitution line from a cross of T. aestivum cv. 7182 and Th. ponticum, was characterized by cytogenetic identification, in situ hybridization, molecular marker analysis, and morphological investigation of agronomic traits and disease resistance. Cytological observations showed that CH10A5 contained 42 chromosomes and formed 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…Markers speci c to Aegilops biuncialis were developed with a success rate of up to 40.33% [51]; The success rate of 1JS-speci c marker development from an alien chromosome of Th. ponticum was 52.98% [52]. The development of SLAF-seq technology has certain practical importance [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Markers speci c to Aegilops biuncialis were developed with a success rate of up to 40.33% [51]; The success rate of 1JS-speci c marker development from an alien chromosome of Th. ponticum was 52.98% [52]. The development of SLAF-seq technology has certain practical importance [32].…”
Section: Discussionmentioning
confidence: 99%
“…[56] used the Cbanding technique to show that chromosomal rearrangement had occurred in 208 tetraploid wheat, 252 hexaploid wheat, and 39 triticale accessions. The introduction of alien chromosomes may lead to changes in the structure of chromosomes of common wheat and affect the expression of a suite of genes [52,59]. Przewieslik-Allen et al [60] analyzed 471 materials and found that chromosome rearrangement plays an important role in the genetic diversity of varieties.…”
Section: Discussionmentioning
confidence: 99%
“…WAWHT2046, RIL143, Avocet-S and F 2 plants from the mapping population were grown in controlled walk-in growth chambers at 24 °C during the day and 22 °C during the night. At the jointing stage, plants were inoculated with fresh urediniospores of race CYR34 mixed with talcum powder at a 1:20 ratio using the shaking off method (Ma et al 2016 ; Wang et al 2020b ). Wheat leaves were uniformly dusted with this mixture of urediniospores and talc.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 914 markers (Table 1), including simple sequence repeat (SSR)/expressed sequence tag (EST), which belonged to the first homologous group (https://wheat.pw.usda.gov/ GG3/), intron targeting (IT) markers (Zhang et al, 2017), and PCR-based landmark unique gene (PLUG) markers (Wang et al, 2020), were synthesized by Sangon Biotech Co., Ltd. and used to identify the homeologous group of the alien chromosomes in SN19647 and compare their identity with those in CH10A5. PCR amplification system was a 10-µL reaction mixture, containing 40 ng genomic DNA, 2 µM each of forward and reverse primers, 2.5 mM each of the dNTPs, 2.5 mM MgCl 2 , 1× PCR buffer (10 mM Tris-HCl, pH 8.5, 50 mM KCl), and 0.5 U Taq DNA polymerase.…”
Section: Molecular Marker Analysismentioning
confidence: 99%
“…Recently, the 1J S chromosome of Th. ponticum in the 1J S (1D) disomic substitution line CH10A5 was reported to be probably responsible for resistance to both powdery mildew and stripe rust (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%